Intermolecular Carbonyl–olefin Metathesis with Vinyl Ethers Catalyzed by Homogeneous and Solid Acids in Flow - Rivero‐Crespo, Miguel Ángel; Tejeda‐Serrano, María; Pérez‐Sánchez, Horacio; Cerón‐Carrasco, José Pedro; Leyva‐Pérez, Antonio (Angewandte Chemie International Edition, 2020)
The carbonyl–olefin metathesis reaction has experienced significant advances in the last seven years with new catalysts and reaction protocols. However, most of these procedures involve soluble catalysts for intramolecular reactions in batch. Herein, we show that recoverable, inexpensive, easy to handle, non‐toxic, and widely available simple solid acids, such as the aluminosilicate montmorillonite, can catalyze the intermolecular carbonyl–olefin metathesis of aromatic ketones and aldehydes with vinyl ethers in‐flow, to give alkenes with complete trans stereoselectivity on multi‐gram scale and high yields. Experimental and computational data support a mechanism based on a carbocation‐induced Grob fragmentation. These results open the way for the industrial implementation of carbonyl–olefin metathesis over solid catalysts in continuous mode, which is still the origin and main application of the parent alkene–alkene cross‐metathesis. Intermolecular carbonyl–olefin metathesis between aromatic ketones/aldehydes and vinyl ethers is accomplished with not only simple soluble but also solid acid catalysts to give trans alkenes in high yields and multigram amounts in‐flow.